One-Stop Device Closure for Ventricular Septal Defect with Atrial Septal Defect Guided by Transesophageal Echocardiography - Jinghao Song; Yuekun Sun; Huaixue Mi; Shibin Sun; Hongxin Li (Reviews in Cardiovascular Medicine)
Background: Ventricular septal defect (VSD) with atrial septal defect (ASD) is a common complex congenital heart disease. This study aimed to evaluate the clinical efficacy and safety of transesophageal echocardiography (TEE)-guided percardiac or combined percutaneous techniques for treating VSD with ASD in patients with varying anatomies. Methods: This retrospective cohort study reviewed 40 cases of VSD with ASD treated in our center from June 2015 to July 2023. Under TEE guidance, peratrial, perventricular, or combined percardiac/percutaneous approaches were used based on the VSD type and secundum-type ASD. Follow-up examinations, including electrocardiography, transthoracic echocardiography, and X-ray, were performed after surgery at 24 hours, 1, 3, 6, and 12 months, and yearly. Results: All patients underwent surgery successfully (100%), with 24, 5, and 11 patients undergoing simultaneous closure via the peratrial, perventricular, and combined percardiac/percutaneous approaches, respectively. Among them, there were six cases of a mild residual shunt, three instances of a mild tricuspid regurgitation, two cases of a mild aortic valve regurgitation, one case of a mild mitral regurgitation, and three cases of an incomplete right bundle branch block, all observed after VSD closure; all had resolved within 6 months of the operation. The chi-square test showed no significant differences in adverse event rates among the three surgical approaches (χ2 = 0.09, df = 2, p = 0.957). The Friedman test compared the preoperative and postoperative left ventricular end-diastolic diameter for the three approaches, providing p < 0.001, p = 0.589, and p = 0.445, respectively. None of the patients required reoperation during the follow-up period. Conclusions: Under TEE guidance, using diverse percardiac or combined percutaneous device closure techniques for the one-stop treatment of different types of VSDs combined with ASD is safe, effective, and feasible. These approaches can be performed as a valuable alternative therapy for selected patients.